Information, Ownership Structure, and Shareholder Voting: Evidence from Shareholder-Sponsored Corporate Governance Proposals - Gordon, Lilli A.; Pound, John (Journal of Finance, 1993)
This paper examines how information and ownership structure affect voting outcomes on shareholder-sponsored proposals to change corporate governance structure. We find that the outcomes of votes vary systematically with the governance and performance records of target firms, the identity of proposal sponsors, and the type of proposal. We also find that outcomes vary significantly as a function of ownership by insiders, institutions, outside blockholders, ESOPs, and outside directors who are blockholders. These results suggest that both public information and ownership structure have a significant influence on voting outcomes.